The Impact of Asian Financial Crisis to Earnings Management and Operating Performance in Malaysia - Rosnia, Masruki; Noor Azlinna, Azizan (Medwell Journals, 2012)
This study is motivated by the emergence of different trend between Cash from Operations (CFO) and net income reported by companies. The objective of this study is to investigate the relationship between the operating performances of top 100 market firms listed on the Main Board of the Bursa Malaysia and the behaviour of net income after Asian financial crisis. Initially the sample firms are divided into 10 portfolios based on relative Cash from Operations (CFO) rankings to test if there are systematic differences in CFO across portfolios. A correlation test and a sign-change ratio test are used to study if operating performances and net income are interrelated. The empirical evidence supports the predictions. It suggests that firms from various industries manage earnings when operating performance is poor. The firms tend to choose income-increasing strategies, specifically when the operating performance is extremely poor. In fact, some firms tend to take a big bath whereas some of the exceptionally well performing firms tend to select income-decreasing strategies.